2016
DOI: 10.1021/acs.jpcb.6b05766
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Proof on Interplay between Trehalose and Guanidinium Chloride for the Stability of Stem Bromelain

Abstract: Guanidinium chloride (GdnHCl), a potential denaturant, is well-known to denature a number of proteins in vitro as well as in vivo studies. Its deleterious action on stem bromelain (BM) is quite prominent resulting decrease in protein structure and stability. The counteraction of this adverse effect of GdnHCl by the use of osmolytes is scarcely studied and the mechanism is still illusive and not exclusive. For the first time, to test elegant and simple counteraction hypothesis as a general mechanism we utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…By the accumulation of low molecular weight organic molecules, a diverse range of organisms from numerous phyla responded to the changes in intracellular water activity resulting from the hostile stresses such as dehydration, temperature variations, variable pH, freezing, high salinity, high concentrations of denaturants. These molecules are termed as osmolytes or osmoprotectants. The methylamines and amino acids are major classes of naturally occurring osmolytes.…”
Section: Introductionmentioning
confidence: 99%
“…By the accumulation of low molecular weight organic molecules, a diverse range of organisms from numerous phyla responded to the changes in intracellular water activity resulting from the hostile stresses such as dehydration, temperature variations, variable pH, freezing, high salinity, high concentrations of denaturants. These molecules are termed as osmolytes or osmoprotectants. The methylamines and amino acids are major classes of naturally occurring osmolytes.…”
Section: Introductionmentioning
confidence: 99%
“…In the hydrophobic core of a folded protein Trp has high fluorescence intensity. In an unfolded protein, Trp is exposed to a polar environment and this results in a decrease in fluorescence (Rani and Pannuru, 2016; Rani and Venkatesu, 2015; Rani and Venkatesu, 2016). The combination of 1 H NMR data and Figure S5 suggested that bromelain and the surfactant together formed a more compact structure via hydrophobic interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on enhancing enzyme activity and stability have always been of great importance for both basic research and industrial applications (Arshad et al, 2014; Manzoor et al, 2016; Rani and Pannuru, 2016; Rani and Venkatesu, 2015; Rani and Venkatesu, 2016; Rathnavelu et al, 2016; Xue et al, 2019). The conformational stability of bromelain increases with increasing polyol size and the proteolytic activity of bromelain changes in the opposite order; among xylitol, erythritol, ethylene glycol, glycerol, and sorbitol, sorbitol is the weakest stabilizer for bromelain whereas it increases the activity of bromelain the most (Rani and Pannuru, 2016; Rani and Venkatesu, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While guanidinium is structurally similar to urea having two amine groups, the exact mechanism by which guanidinium destabilizes proteins is largely unknown. [ 18–22 ] Moreover, there has been a great deal of controversy surrounding the molecular interactions between denaturants such as guanidinium and stabilizing osmolytes such as TMAO. One popular theory suggests that the stabilization of proteins is mediated through the direct interaction between the osmolyte and the protein, [ 12,23,24 ] which is commonly known as the “direct effect.” [ 25–30 ] Conversely, other studies have concentrated on the effects that the osmolyte has on hydrogen‐bonded water networks, which has been shown to affect the stability of the protein through the rearrangement of the solvation shell.…”
Section: Introductionmentioning
confidence: 99%